Menalar Kisah Dipilihnya Daud Menggantikan Saul dari Pemaknaan Kaum Pentakostal - Kosma Manurung; Steven Tommy Dalekes Umboh (Sabda: Jurnal Teologi Kristen, 2023)
God's action in sending Samuel to anoint David to be king in place of Saul, was not a reckless action born of occasional emotion. Desiring, Allah has a strong reason for His actions. Saul's disobedience to God's commands was suspected to be the cause of God impeaching him from the position of king and replacing him with David. This research seeks to reason out the story of David's choice to replace Saul as king of Israel through the anointing of the prophet Samuel in 1 Samuel 16:1-13 from the meaning of the Pentecostals. The use of qualitative narrative methods and support from literature studies are expected to be able to provide a strong, thorough, and systematic understanding of the review of the reconstructive background of David's election as king, the narrative of David's election in 1 Samuel 16, and the meaning of the Pentecostals about the story of David's election. It was concluded that for Pentecostals this story provides an important lesson to always live in obedience to God, see God's decrees from the right perspective, the need for believers to guard their hearts, because its existence represents the presence of God. Abstrak:Tindakan Allah yang mengirim Samuel untuk mengurapi Daud menjadi raja menggantikan Saul, bukanlah tindakan yang sembrono yang lahir dari emosi sesaat. Melainkan, Allah memiliki alasan kuat atas tindakanNya tersebut. Ketidaktaatan Saul pada perintah Allah ditengarai menjadi penyebab Allah memakzulkannya dari posisi raja dan menggantikannya dengan Daud. Adapun penelitian ini berupaya menalar kisah dipilihnya Daud menggantikan Saul menjadi raja Israel melalui pengurapan nabi Samuel dalam 1 Samuel 16: 1-13 dari pemaknaan kaum Pentakostal. Penggunaan metode kualitatil naratif serta suport dari kajian litaratur diharapkan mampu memberikan pemaman yang kuat, teliti, dan sistematik terkait ulasan reka ulang latar belakang pemilihan Daud menjadi raja, narasi pemilihan Daud dalam 1 Samuel 16, dan pemaknaan kaum Pentakostal tentang kisah pemilihan Daud ini. Disimpulkan bahwa bagi kaum Pentakostal kisah ini memberikan pelajaran pentingnya untuk selalu hidup dalam ketaatan terhadap Allah, melihat ketetapan Allah dari perspektif yang benar, perlunya orang percaya menjaga hati, karena keberadaannya mewakili kehadiran Allah.   Kata Kunci: Daud; kisah Daud; pilihan Allah; teologi pentakostal; 1 Samuel 16